2020
DOI: 10.3390/land9010013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Bund and Stone-Faced Soil Bund on Soil Physicochemical Properties and Crop Yield Under Rain-Fed Conditions of Northwest Ethiopia

Abstract: Research-based evidence on the effects of soil and water conservation practices (SWCPs) on soil physicochemical properties and crop yield is vital either to adopt the practices or design alternative land management strategies. Thus, this study was conducted to evaluate the effects of about 10-year-old soil bund (SB) and stone-faced soil bund (SFSB) structures on selected soil physicochemical properties, slope gradient, barley grain yield, and yield components in the Lole watershed, in the northwest highlands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 38 publications
13
71
0
Order By: Relevance
“…In addition, a research-based evidence on the effects of SWC practices on soil physicochemical properties in the northwest highlands of Ethiopia 59 indicated that SWC practices tended to increase soil fertility and most of the soil chemical properties showed relative change with landscape positions. Guadie et al 59 highlighted that raising awareness and convincing farmers toward SWC practice is essential for future sustainable land management. Other studies conducted to assess variations in soil properties under different LUTs in southern Ethiopia 60 supported our finding and indicated that change in LUT, slope category, and management practice significantly affected soil textural fraction (silt, sand, and clay), soil pH, EC, OC, bulk density, and TN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a research-based evidence on the effects of SWC practices on soil physicochemical properties in the northwest highlands of Ethiopia 59 indicated that SWC practices tended to increase soil fertility and most of the soil chemical properties showed relative change with landscape positions. Guadie et al 59 highlighted that raising awareness and convincing farmers toward SWC practice is essential for future sustainable land management. Other studies conducted to assess variations in soil properties under different LUTs in southern Ethiopia 60 supported our finding and indicated that change in LUT, slope category, and management practice significantly affected soil textural fraction (silt, sand, and clay), soil pH, EC, OC, bulk density, and TN.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a research-based evidence on the effects of SWC practices on soil physicochemical properties in the northwest highlands of Ethiopia 59 indicated that SWC practices tended to increase soil fertility and most of the soil chemical properties showed relative change with landscape positions. Guadie et al 59 highlighted that raising awareness and convincing farmers toward SWC practice is essential for future sustainable land management.…”
mentioning
confidence: 99%
“…Consequently, this leads to a loss of soil fertility, soil quality, and loss of ecosystem services [120]. It should be noted, however, that extensive soil loss is not limited to vineyards; different authors have reported similar problems in various other crops [121][122][123][124]. Research has suggested that soil loss in vineyards is above the level that amounts to tolerable soil loss, less so for older vineyards with more organic matter content and higher bulk density in relation to younger vineyards [125] Moreover, accurately measuring soil loss in vineyards is fraught with difficulties, because different methodologies available tend to give different results.…”
Section: (Un)sustainable Agronomic Management and Resulting Soil Lossmentioning
confidence: 99%
“…Rotating or intercropping cassava with catch crops, including legumes that can fix nitrogen from the atmosphere, can further mitigate soil erosion (Cerdà, Rodrigo‐Comino, Giménez‐Morera, Novara, et al, 2018; Cerdà, Rodrigo‐Comino, Novara, Brevik, et al, 2018; Cerdà, Rodrigo‐Comino, Giménez‐Morera, & Keesstra, 2018). These catch crops will produce biomass that turns into residues or mulch, which protects the soil from water erosion, helps sequester soil carbon and retain nutrients, promotes topsoil aggregation, enhances infiltration and restores soil health (Cerdà, Rodrigo‐Comino, Giménez‐Morera, Novara, et al, 2018; Guadie, Molla, Mekonnen, & Cerdà, 2020; Keesstra et al, 2018; Rodrigo‐Comino et al, 2019). Over time, the land will become fertile and allow for planting trees, such as cacao.…”
Section: Year Production In Million Tons Producer Price In Usd/ionmentioning
confidence: 99%